Challenges in Abdominal Organ Transplantation During the COVID-19 Pandemic - Esagian, Stepan M.; Ziogas, Ioannis A.; Giannis, Dimitrios; Hayat, Muhammad H.; Elias, Nahel; Tsoulfas, Georgios (Frontiers in Medicine, 2020)
As the coronavirus disease 2019 (COVID-19) outbreak has rapidly evolved into a global pandemic, abdominal organ transplantation programs are currently facing multiple challenges. Transplant candidates and recipients are considered high-risk populations for severe disease and death due to COVID-19 as a result of their numerous underlying comorbidities, advanced age and impaired immune function. Emerging reports of atypical and delayed clinical presentations in these patients generate further concerns for widespread disease transmission to medical personnel and the community. The striking similarities between COVID-19 and other outbreaks that took place over the past two decades, like Severe Acute Respiratory Syndrome and Middle East Respiratory Syndrome, highlight the severity of the situation and dictate that extra measures should be taken by the transplant programs to avoid adverse outcomes. Transplant organizations are currently calling for strict screening and isolation protocols to be established in all transplant programs, for both organ donors and recipients. As the situation escalates, more radical measures might be necessary, including a temporary hold on non-urgent transplantations, resulting in serious ethical dilemmas between the survival of these patients and the safety of the community. Further data about these special populations could result in more individualized guidelines for abdominal organ transplantation in the era of COVID-19.